Design and Analysis of Isolation Improvement and Compact Size of SPDT Switch with Switchable Open Stub Resonator for Wireless Communication - Noor Azwan, Shairi; Badrul Hisham, Ahmad; Peng Wen, Wong; Zakaria, Zahriladha (Buldanshahr : IJECSE, 2013)
Two new designs of switchable microstrip line open stub resonator are proposed for isolation improvement of SPDT discrete PIN diode switch which is targeted for wireless communication such as WiMAX and LTE application at 3.5 GHz band. Despite of isolation improvement, the second design of the resonator can reduce overall size of SPDT discrete PIN diode switch. The PIN diodes are based on commercialize single PIN diode in SOD523 package. The solutions are for microstrip line based circuit design with low performance discrete PIN diode and low cost printed circuit board using FR4 material to achieve isolation higher than 30 dB. Firstly, the conceptual and operation of the proposed resonators are discussed using mathematical modeling. The isolation improvement using microstrip line open stub resonator is modeled and analyzed based on two-port network. Then, two different SPDT discrete PIN diode switches with switchable microstrip line open stub resonator are demonstrated. The simulated results and the measured results agree well for both designs where it shows improvement of isolation higher than 30 dB and the second design is able to reduce 34% of the total circuit size compared with the first design.